Penguatan Pelayaran Rakyat sebagai Bagian dari Konektivitas di Indonesia - Budi Hidayat (Bappenas Working Papers, 2019)
Indonesia is the world's largest archipelagic country in the world, therefore demand for sea transportation is very important. Sea transport being very strategic since it plays a role in connecting one island to another island and marine transport is a tool for economic activity. As a subsystem of national shipping, traditional shipping plays a role in the distribution of goods to and from isolated areas. In addition, traditional shipping also acts as a feeder for larger vessels. Nowadays, traditional shipping is experiencing obstacles concerning cargo and lack of wood as the main material for the ship. In order to maintain the traditional shipping as a national cultural heritage, policies are needed, especially revitalization of traditional shipping and rejuvenating existing vessels with stronger material (non-wood). This Paper discusses how scenarios are made in order to identify, anticipate and assess policy choices in the future. In the end, the policy can be analyzed to what extent the Traditional Shipping can support Sea Tolls.